Staff training in physical interventions: a literature review - McDonnell, Andrew A.; O’Shea, Marion C.; Bews-Pugh, Stephanie J.; McAulliffe, Hannah; Deveau, Roy (Frontiers in Psychiatry, 2023)
Abstract Background: The restraint and seclusion of individuals in care environments is controversial, but are used frequently by frontline staff in a variety of care settings, including psychiatric, IDD, older adults, and children’s services. Physical restraint has been associated with emotional harm, physical injury to staff and consumers, and has even resulted in death of individuals in care environments. Various interventions have been implemented within care settings to reduce restraint, many of these interventions focus on multi-component elements. One of the most common interventions is staff training that includes some form of physical interventions to support individuals to manage crises situations. There is little evidence to support the effectiveness and application in the literature (1). This review will examine the literature across all care environments. Methods; A systematic search was conducted following PRISMA guidelines using Cochrane Database, Medline EBSCO, Medline OVID, PsychINFO, and the Web of Science. Main search keywords staff training, physical intervention, physical restraint. The MMAT was utilised to provide an analytical framework for the included studies. Results and Discussion: Seventeen articles were included in the literature review. Studies on the effects of staff training in physical interventions within care services comprise a wide range of outcomes and designs. Training programmes utilised vary widely in their duration, course content, teaching methods, and extent that physical skills are taught. Studies were of relatively poor quality. Many descriptions of training programmes did not clearly operationalize the knowledge and skills taught to staff. As such it is difficult to compare course content across the studies. Few papers operationally described the physical disengagement (breakaway) skills and restraint procedures in sufficient detail. Although staff training is a ‘first response’ to managing health and safety, there is very little evidence that staff training in physical interventions is an effective intervention. At present, the vast majority of training in physical interventions that takes place around the world could be described by researchers as in effect ‘unlicensed products’.